DARI RITUAL KE IDENTITAS: ANALISIS HISTORIS-TEOLOGIS MAKNA SOSIAL PERJAMUAN KUDUS - Purba, Daniel Rizki (Diegesis : Jurnal Teologi, 2025)
This study aims to explore the social identity constructed by the Sacrament of the Holy Communion. The main issue stems from the fact that the Holy Communion, often viewed as the essence and center of theology, is understood merely as a ritual that impacts only the relationship between God and humanity. As a result, the social meaning of the Holy Communion is lost, creating social gaps within the church as it fails to have a direct impact on the actual social life of the congregation. Therefore, this research seeks to delve into the social-historical and social-theological aspects to uncover the social values of the Holy Communion based on the development of the communion and the doctrines that have discussed it. The findings reveal that, although rarely associated with social values in society, the Holy Communion plays a significant role in shaping human social identity, specifically the identity of the communion community. Thus, the Holy Communion is a fundamental element in forming and structuring human social identity by calling them into the communion as the communion community.